Analisis Penalaran Ilmiah Mahasiswa Jurusan Pendidikan Guru Madrasah Ibtidaiyah (PGMI) IAIN Pekalongan - Shilla, Rhischa Assabet; Andrea Faktur Rahman; Dewi Zahrotul Afida (Indonesian Journal of Islamic Elementary Education, 2022)
The aim of this study is to know the ability level of scientific reasoningability of the 6th-semester students in the PGMI study program, IAIN Pekalongan. Scientific reasoning is one of the ability that should be owned by each teacher to be able to familiarize students to find a concept knowledge through how to think as a scientist.This study uses descriptive method. The total sample of this study is 70 students. Students’ scientific reasoningability was measured by test that adapted from Modified Lawson Classroom Test of Scientific Reasoning (MLCTSR). MLCTSR consist of 12 two-tier multiple choice questions. MLCTSR consists of six aspects, i.e., conservation of mass and volume, proportional reasoning, controlling the variable, probabilistic reasoning, correlational reasoning, and hypothetical deductive reasoning. The result of this research shows that the levels of students’ scientific reasoning skills were classified into three categories, i.e., 85,71% concrete operational, 10% transitional operational, and 4.29% formal operational. Scientific reasoning aspect has not understood yet by most of the students was proportional reasoning and controlling variable aspect. As for the aspects that understand well by students was conservation of mass and volume.